Pemilihan Media Sosial Promosi PMB UPY dengan Metode Weight Product - Muhammad Fairuzabadi; Firdiyan Syah; Tri Hastono (Jurnal Dinamika Informatika, 2023)
This research aims to analyze the selection of social media for promoting the Master's Program (PMB) at the University of PGRI Yogyakarta (UPY) and develop a decision support system using the Weight Product method. The emergence of social media has brought new opportunities in the field of marketing, including PMB promotion at UPY. However, the success of promotions highly relies on choosing the right social media platforms. In this study, an evaluation is conducted on five popular social media platforms, namely Facebook, Instagram, Twitter, YouTube, and LinkedIn. The criteria used include the number of active users, target audience, promotional features, interaction level, and advertising costs. The weights for these criteria are determined through preliminary surveys and discussions with relevant experts. The Weight Product method is employed to calculate the ranking of social media platforms based on the criteria weights. Data is collected through online surveys administered to prospective students and analyzed using specialized software. The results of the analysis indicate that Instagram is the most suitable social media platform for PMB promotion at UPY, followed by Facebook and YouTube. This research provides a better understanding of how social media can be effectively utilized for PMB promotion at UPY. The developed decision support system can assist marketing staff in making better choices in selecting social media platforms for PMB promotion. The findings of this study are expected to enhance the effectiveness of promotions and the competitiveness of the PMB at UPY. Keywords: social media, promotion, Master's Program (PMB), Weight Product, Universitas PGRI Yogyakarta (UPY)